Effects of thyroid status on HbA1c - Sivaranjani Ambalavanan; Sathya Selvarajan; K. Sowmya (Journal of Research in Clinical Medicine)
Introduction: Altered erythrocyte turnover may not adequately reflect the glycemic status in the glycated hemoglobin (HbA1c) levels. Hypothyroidism is one such condition that might cause reduced erythropoiesis and falsely high HbA1c values. The aim of the study is to evaluate the effect of thyroid hormone on HbA1c levels on non-diabetic hypothyroid individuals and also to evaluate HbA1c levels in hypothyroid individuals with diabetes and to compare them with normal healthy subjects. Methods: This prospective study was conducted on 210 individuals, of whom 70 were assigned to group I- hypothyroid individuals, 70 to group II- hypothyroid individuals with diabetes, and 70 to group III—Normal individuals. Following data regarding laboratory investigations were collected which included fasting blood sugar (FBS), postprandial blood sugar (PPBS), HbA1c, free triiodothyronine (fT3), free thyroxine (fT4), and thyroid stimulating hormone (TSH). Data analysis was performed using SPSS version 16.0. Results: The median level of HbA1c was significantly higher in hypothyroid than in normal individuals (5.6 [5.5-5.7] % vs 5.2 [5-5.3] %, P≤0.001). The median level of TSH was significantly higher in hypothyroid than in normal individuals (11.13 [6.9-22.9] μIU/mL vs 2.15 (1.33-1.60) μIU/mL). The serum level of HbA1c was significantly positively correlated with TSH in hypothyroid individuals (r=0.281, P≤0.01). Conclusion: There is a positive correlation between HbA1c and TSH, and a negative correlation between HbA1c and fT4 levels. Serum HbA1c levels were significantly higher in hypothyroid individuals than the normal individuals. Therefore, our study suggests that we should proceed with caution while interpreting HbA1c levels in individuals with hypothyroidism.